Answer:
![m-n=2](https://tex.z-dn.net/?f=m-n%3D2)
Step-by-step explanation:
Instead of using the standard form, we can use the vertex form of a quadratic equation:
![f(x)=a(x-h)^2+k](https://tex.z-dn.net/?f=f%28x%29%3Da%28x-h%29%5E2%2Bk)
Where a is the leading coefficient, and (h, k) is our vertex.
Our vertex point is at (2, -4). So, let’s substitute 2 for h and -4 for k:
![f(x)=a(x-2)^2-4](https://tex.z-dn.net/?f=f%28x%29%3Da%28x-2%29%5E2-4)
Now, we need to determine a.
We know that it passes through the point (4, 12). So, when x is 4, y must be 12. In other words:
![12=a((4)-2)^2-4](https://tex.z-dn.net/?f=12%3Da%28%284%29-2%29%5E2-4)
Solve for a. Subtract within the parentheses:
![12=a(2)^2-4](https://tex.z-dn.net/?f=12%3Da%282%29%5E2-4)
Add 4 to both sides:
![16=a(2)^2](https://tex.z-dn.net/?f=16%3Da%282%29%5E2)
Square:
![16=4a](https://tex.z-dn.net/?f=16%3D4a)
Solve:
![a=4](https://tex.z-dn.net/?f=a%3D4)
Thererfore, the value of a is 4.
So, our function is:
![f(x)=4(x-2)^2-4](https://tex.z-dn.net/?f=f%28x%29%3D4%28x-2%29%5E2-4)
Now, let’s find our roots. Set the equation to 0 and solve for x:
![0=4(x-2)^2-4](https://tex.z-dn.net/?f=0%3D4%28x-2%29%5E2-4)
![4=4(x-2)^2\\1=(x-2)^2\\x-2=\pm1 \\ x=2\pm1 \\ x=3\text{ or } 1](https://tex.z-dn.net/?f=4%3D4%28x-2%29%5E2%5C%5C1%3D%28x-2%29%5E2%5C%5Cx-2%3D%5Cpm1%20%5C%5C%20x%3D2%5Cpm1%20%5C%5C%20x%3D3%5Ctext%7B%20or%20%7D%201)
So, our roots are 1 and 3.
The greater root is 3 and the lesser root is 1.
Therefore, m-n, where m>n, is 3-1 or 2.
Our final answer is 2.